2016
DOI: 10.1007/s40279-016-0570-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Exercise Training in Hypoxia Versus Normoxia on Vascular Health

Abstract: Based on current published studies, hypoxic ExT potentiates vascular adaptations related to skeletal muscle capillarization and dilator function. These findings may contribute to establishing effective exercise programs designed to enhance vascular health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 68 publications
1
31
1
Order By: Relevance
“…Systemic oxygen deficiency may facilitate endurance-type exercise-induced adaptation (Montero & Lundby, 2016). In our current study, although WBV + BFR elicited a significantly greater HR response versus the non-BFR WBV condition, neither WBV nor WBV + BFR sessions caused significant changes in SpO 2 .…”
Section: Discussioncontrasting
confidence: 60%
“…Systemic oxygen deficiency may facilitate endurance-type exercise-induced adaptation (Montero & Lundby, 2016). In our current study, although WBV + BFR elicited a significantly greater HR response versus the non-BFR WBV condition, neither WBV nor WBV + BFR sessions caused significant changes in SpO 2 .…”
Section: Discussioncontrasting
confidence: 60%
“…While RSA training is well accepted to improve this quality, 5 utilizing RSA in hypoxic conditions (the so-called "repeated-sprint training in hypoxia", RSH) has shown superior results when comparing to similar training in normoxia (RSN) 6 in several sports [7][8][9][10] . It should be noted that while the majority of studies have shown positive RSA results when comparing RSH to RSN, 6 there is still some debate on the overall effectiveness of RSH as well as debate on the mechanisms for the performance increase 11,12 . It has been speculated that the main underlying mechanism relies on the peripheral compensatory vasodilation in response to the hypoxia-induced hypoxemia, inducing a better resistance to fatigue in fast-twitch fibres, hence increasing the ability to repeat short bouts of exercise at maximal intensity 13 out that RSH has also a positive impact on anaerobic and glycolytic pathway as shown previously 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Regular exercise training has an important impact on autonomic nervous system (ANS) function [1], improving cardiac parasympathetic regulation, reducing sympathetic tone, increasing baroreflex sensitivity and heart rate variability (HRV), further providing protective effects against cardiovascular and metabolic diseases [1,2] and reducing all-cause mortality [3,4]. Hypoxic exercise (i. e. exercise under reduced oxygen availability) has been shown to represent a valid alternative to normoxic exercise to provide an adequate training stimulus, promoting beneficial physiological training adaptations as well as positive healthrelated outcomes [5][6][7]. Nowadays, hypoxic exercise is implemented within training programs of different populations [5,[7][8][9].…”
Section: Introductionmentioning
confidence: 99%